Disease and medicine in India : a historical overview - Indian History Congress 2001 : Calcutta, India); Kumar, Deepak, 1952- ([Aligarh] : Indian History Congress ; New Delhi : Tulika, 2001)
Seminar papers presented at a special panel in 61st session of Indian History Congress held at Kolkota, 1-3 Jan. 2001.
Includes bibliographical references (p. 276-289) and index.
Mode of access: Internet.
Keywords: Medicine, Popular -- Congresses; Herbs -- India -- Therapeutic use -- Congresses; Traditional medicine -- India -- Congresses